Re-ascent triggered high-altitude pulmonary and cerebral edema in a Tibetan with pre-existing high-altitude polycythemia: a Case Report - Huang, He; Yuan, Shuaijun; Zhang, Limin; Song, Jiaye; Xue, Dengwei; Liu, Dongmei; Cao, Jingxin (Frontiers in Physiology, 2026)
High-altitude pulmonary edema (HAPE), high-altitude cerebral edema (HACE), and high-altitude polycythemia (HAPC) are each rarely observed in Tibetan populations. The coexistence of HAPE, HACE, and HAPC in the same person has not been previously documented. Here, we report the case of a native Tibetan male with HAPC who developed both HAPE and HACE upon re-ascent to an altitude of 3,650 m after a 27-day stay at low altitude. On the 3rd-4th day post-return, the patient exhibited persistent dyspnea, chest tightness, hypersomnia, intermittent agitation, and confusion. Chest CT and multimodal neuroimaging confirmed the presence of HAPE and HACE. Treatment followed guidelines (supplemental oxygen, high-dose dexamethasone) along with supportive measures, resulting in clinical resolution. This is the first reported case of co-occurring HAPE, HACE and HAPC in a native Tibetan upon re-ascent, suggesting that pre-existing HAPC may be a significant risk factor for severe acute high-altitude illness in this setting.